Gamal sebagai Pakan Konsentrat Hijau Desa Salut, Kecamatan Kayangan, Kabupaten Lombok Utara, Nusa Tenggara Barat - Muhamad Sukri; Maulana Ishak (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Salut Village Kayangan Sub-District North Lombok Regency West Nusa Tenggara is one of the villages with the impact of the earthquake in 2018 which was quite badly affected. The impact caused by the earthquake included damage to infrastructure, houses, the cut off of clean flow, disruption of farming and agricultural activities. The disruption of agricultural and plantation activities caused disruption to the economic activities of the Village of Salut as a whole. The agriculture and plantation sectors are the source of income for the Salut Village community, plantation products in the form of coconuts, cocoa, cashew, coffee, corn and rice. The livestock sector is one of the supports in the farmer's business. Livestock raised by farmers are bali cows and simental cross cows, cows that are kept are cows with the purpose of maintenance as savings, the number of ownership is between two to five cows per person, the ownership of cows is influenced by the ability of farmers to provide animal feed. The food provided is in the form of grass and agricultural waste and tree legumes such as gamal. Utilization of local feed has not been used optimally especially during the rainy season, availability of feed during the rainy season is abundant while during the dry season the availability of feed is very limited, so it is necessary to process fermented feed to repeat excess feed during the rainy season. The use of tree legumes such as gamal needs to be optimized as a green concentrate feed to meet the nutritional needs of cattle.